Cardiorenal Anemia Syndrome and Survival among Heart Failure Patients in Tanzania: A Prospective Cohort Study. Issue 1 (December 2017) - Pallangyo, Pedro; Fredrick, Francis; Bhalia, Smita; Nicholaus, Paulina; Kisenge, Peter; Mtinangi, Benjamin; Janabi, Mohamed; Humphrey, Stephen
Abstract Background Cardiorenal anemia syndrome (CRAS) is an evolving global epidemic associated with increased morbimortality and cost of care. The management of patients with CRAS remains a challenging undertaking worldwide and the lack of evidence-based clinical guidelines adds to the challenge. We aimed to explore the prevalence and survival rates of heart failure patients with CRAS in Tanzania. Methods We screened 789 patients and consecutively recruited 463 who met the inclusion criteria. Each participant underwent an interview, physical examination, anthropometric measurements, anemia, renal functions and echocardiographic assessment. All participants were followed until death or for up-to 180 days, whichever came first. Bivariate comparison and subsequent Cox proportional-hazards regression model were used to compare the CRAS and non-CRAS groups with respect to the primary end point. Results The mean age of participants was 46.4 ± 18.9 years, and 56.5% were women. Overall, 51.9% of participants had renal insufficiency, 72.8% were anemic and 44.4% had CRAS. During a mean follow-up of 103 ± 75 days, 57.8% of participants died. Patients with CRAS displayed a higher mortality rate (73.5%) compared to those free of CRAS (45.8%), (p  < 0.001). During multivariate analysis in a cox regression model of 21 potential predictors of mortality; renal dysfunction (HR 1.9; 95% CI 1.0–3.5;p  = 0.03), severe anemia (HR 1.8; 95% CI 1.0–3.1;p  = 0.04), hyponatremia (HR 2.2; 95% CI 1.3–3.7;p  = 0.004) and rehospitalization (HR 4.3; 95% CI 2.2–8.4;p  < 0.001) proved to be the strongest factors. Conclusion Cardiorenal anemia syndrome is considerably prevalent and is associated with an increase in mortality amongst patients with heart failure. In view of this, timely, aggressive and collaborative measures to improve renal functions and/or correct anemia are crucial in the management of CRAS patients. Furthermore, these findings call for guideline committees to revise and/or develop evidence-based recommendations for management of patients with CRAS.